The issues of increasing the local self-government efficiency in the Republic of Kalmykia - ASHTAEVA, Saglar S.; SHOVAEVA, Maria V.; ASHTAEV, Yuriy S.; DERYUGINA, Tatiana V.; TSUGLAEVA, Nina V. (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
For the time past since the adoption of the Federal Law No. 131-FZ, there emerged problems impeding the effective development of local self-government. In our opinion, the process of differentiation and clarification of powers between levels of public authorities, including between municipal districts and settlements on the municipal level is not completed, as well as the problem of achieving consistency between the financial needs of municipalities for solving matters of local significance and provided financial sources yet is not solved.
Keywords: local self-government, public authorities, municipalities, legislation system